Cost-effectiveness of polatuzumab vedotin in relapsed or refractory diffuse large B-cell lymphoma. Issue 14 (5th December 2020) - Patel, Kishan K.; Isufi, Iris; Kothari, Shalin; Foss, Francine; Huntington, Scott
Abstract: A recent phase II trial showed that use of polatuzumab vedotin in combination with bendamustine plus rituximab (Pola-BR) in transplant-ineligible patients with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) resulted in longer progression-free survival and overall survival compared to bendamustine plus rituximab (BR) alone. In this study, we constructed a Markov model to assess the cost-effectiveness of Pola-BR versus BR in transplant-ineligible R/R DLBCL. We calculated the incremental cost-effectiveness ratio (ICER) of each treatment strategy from a US payer perspective, using a lifetime horizon and a willingness-to-pay threshold of $100, 000 per quality-adjusted life-year (QALY). Use of Pola-BR was associated with an incremental cost of $92, 641 compared to BR alone ($200, 905 vs $108, 265, respectively), an incremental effectiveness of 1.76 QALYs (2.35 vs 0.59 QALYs, respectively), and an ICER of $52, 519/QALY. These data suggest that use of Pola-BR for R/R DLBCL is likely to be cost-effective compared to BR alone.